Faculty use of Twitter in higher education teaching. (6th February 2017) - Hull, Kevin; Dodd, Julie E.
Abstract : Purpose: The purpose of this paper is to determine how higher education teachers are using Twitter in their classroom to engage, educate, and inform students. The results were measured against Chickering and Gamson (1987) "Seven principles for good practice in undergraduate education." Design/methodology/approach: A survey was sent to college and university educators throughout the country who were identified as teachers who use Twitter in their classroom. These educators were asked about their Twitter use, their opinions of Twitter, the impact the social network has had on student learning, the students' reactions to using Twitter, and how Twitter supported pedagogical best practices, including the "Seven principles for good practice in undergraduate education". Findings: The educators reported that student response to using Twitter in the classroom was overwhelmingly positive and that Twitter has positively impacted student learning. The results also indicate that college educators consider that Twitter use in classes does support the seven principles. Research limitations/implications: While college instructors from a wide range of institutions, locations, subject types, and experience levels were surveyed, a limitation is that only their opinions are being examined. Future research may wish to examine the Twitter accounts of these professors to determine if they are using Twitter in the manner that they think they are. Results from the survey could then be compared with the tweet content. Originality/value: While previous research has examined how students use and appreciate Twitter in the classroom, this is one of the first studies to examine how the social network is implemented from an instructor viewpoint. The results demonstrate value to instructors. For instructors, the value lies in the knowledge that Twitter has had a positive impact on classroom success for students and that using the social network promotes best practices in pedagogy, supporting constructivism, experiential learning, and the "Seven principles for good practice in undergraduate education". For administrators, the value lies in the fact that many instructors have had success using Twitter and that more should be encouraged to do the same in their classrooms.